The Role Of The Islamic Republic Of Iran In The Middle East At The End Of The 20th Century - Rustamovich , Tokhtiev Shukhrat (Pubmedia Social Sciences and Humanities, 2024)
The article examines changes in the political life of the Islamic Republic of Iran in the Middle East at the end of the 20th century, namely, the conduct of an independent foreign policy by the president without the approval of other authorities (the clergy are meant). As a result, Tehran began to fulfill its foreign policy tasks, and this in turn contributed to maintaining friendly relations with the Arab monarchies of the Persian Gulf.